An assessment of Bengoh dam overtopping scenario - Heng Hock Hwee; Hii Ching Poon; Kho Kai Tze (Geomatics, Natural Hazards & Risk, 2014)
Dams are supposedly designed and built with stringent criteria for no overtopping under the most adverse meteorological event. This may not be the case for dams that were built earlier before current methodological guidelines and practices are followed. The objective of assessing the safety criteria, i.e., overtopping of the Bengoh dam structure was achieved by carrying out the independent tasks of derivation of probable maximum precipitation (PMP) by reviewing other studies and works in Malaysia: a PMP-to-PMF (probable maximum flood) routing using a modified version of the synthetic unit hydrograph approach and a conventional reservoir routing procedure, i.e., modified Puls procedure to estimate the flood rise during a fateful PMP/PMF event. In essence, the task carried out is to evaluate and assess the adequacy of the step spillway capacity of the Bengoh dam. Bengoh dam, which is made of rolled compacted concrete (RCC) with a step spillway, is considered safe in the event of a PMP/PMF event, with a flood rise generally lower than the embankment crest level, i.e., +86.2 m MSL (mean sea level).